Analisis Kesalahan Penulisan Hamzah dalam Abstrak Skripsi Mahasiswa PBA UIN Jakarta - Faizah, Tiara Putri; Annas, Azwar; Darmawan, Muhammad Rizky; Rahmawati, Siti Uriana; Umbar, Kisno (Universitas Islam Ahmad Dahlan Sinjai, 2024)
The lack of accuracy of PBA students causes deviations in imla' rules in writing Arabic scientific papers. In fact, after studying for 4 years, students should be able to minimize errors in writing. Arabic has become an international language that is studied by various groups. For foreign speakers of Arabic may experience difficulties both in pronunciation and writing. This research is an error analysis research that aims to identify hamzah writing errors in the thesis abstracts of Arabic Language Education Study Program students of UIN Syarif Hidayatullah Jakarta. This research was conducted by using descriptive qualitative method in data processing. The findings of this study reveal the fact that there are still some common mistakes made by PBA students in writing hamzah in an Arabic word. Based on the research that has been conducted using 25 sample data, 42 errors were found which are divided into 7 categories. The most mistakes are found in the 4th category, namely the use of hamzah in isim mashdar from fi'il khumasi and sudasi. With the discovery of many errors in the writing of hamzah, it is necessary to further explore the rules of imla', especially in the writing of hamzah.